Possibility of intrinsic muscle contractile properties in force summation and postactivation potentiation as indices of maximal muscle strength and muscle fatigue. Issue 6 (20th March 2013) - Ohta, Yoichi; Takahashi, Kyohei; Matsubayashi, Takeo
<x xml:space="preserve">Abstract</x> Introduction We investigated whether intrinsic muscle contractile properties in force summation and postactivation potentiation (PAP) can be used as indices of maximal muscle strength and muscle fatigue. Methods Twelve men participated in this study. The maximum voluntary contraction torque (MVC), torque evoked by several stimulations in the tibialis anterior (TA) muscle, force summation parameters, and PAP were evaluated with the progression of fatigue. The force summation parameters were evaluated with respect to responses of single, double, and triple stimulations. Results The percent decreases in the evoked torque parameters with or without PAP were greater than those during MVC. Force summation parameters were significantly related to MVC and fatigue resistance. Conclusions Intrinsic muscle contractile properties with or without PAP in the TA overestimate fatigue during MVC. However, force summation parameters can be used as indices of maximal muscle strength with or without fatigue and fatigue resistance capacity. Muscle Nerve 47: 894–902, 2013